PERENCANAAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING (MRP) PRODUK SERAGAM TINGKAT SLTA PADA UNIT USAHA DUTA COLLECTION SENGONAGUNG PASURUAN - Nuriyanto; Saisuddin (Department of Industrial Engineering - Universitas Yudharta Pasuruan)
The Material Requirement Planning (MRP) method is used to control the supply of raw materials in a company. A company to implement policies in raw material planning must have the right calculation so that there are no advantages and disadvantages in the supply of raw materials. This study aims to determine whether the application of the Material Requirement Planning (MRP) method in the "Duta Collection" business unit in planning the supply of raw materials can run effectively and efficiently. Material requirements planning using MRP method in this paper uses the lot sizing method, where the lot sizing methods used are Lot-for-Lot, and Economic Order Quantity (EOQ), as well as using the Exponential smoothing and least squares forecasting formula as a reference for know the amount of raw material needs in the future. From the calculation of the cost of raw materials in 2016 the total cost of raw material inventories incurred by the Duta Collection business unit was Rp12,797,247,650. Whereas by using the MRP method the total cost incurred was the Lot-for-lot Method of Rp 35,904,531,000 and the Economic Order Quantity (EOQ) Method of Rp 5,886,092,567. From the two MRP methods above, it can be seen that the Economic Order Quantity (EOQ) method has the lowest total inventory cost of Rp 5,886,092,567, - meaning the company can minimize inventory costs by 2.2% of the costs incurred. So as such it is proven that one of these MRP methods can play a role in efficient cost of raw material inventory in the Duta Collection business Unit.